Problematika Gadai Sawah di Kecamatan Tamanan Kabupaten Bondowoso dalam Perspektif Hukum Ekonomi Syariah - Tri Nadhirotur Roifah (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2019)
The practice of sawah (paddy field) mortgage in Tamanan district has been going on for generations. The society considers that the implementation of this sawah (paddy field) mortgage as an appropriate alternative and solution of financing. In fact, it often causes problems between both parties; despite it is completed with written evidence and witnesses in its implementation.The research problem in this study is: How is the practice of sawah (paddy field) mortgage in Tamanan district, Bondowoso regency. How is the practice of sawah (paddy field) mortgage in the perspective of sharia economic law. How are the solutions for the practice of sawah (paddy field) mortgage in Tamanan district, Bondowoso regency in the perspective of sharia economic law. The aim of this study is to describe the practice of sawah (paddy field) mortgage in Tamanan district, Bondowoso regency, to describe sawah (paddy field) mortgage in the perspective of sharia economic law and to describe the solutions for the practice of sawah (paddy field) mortgage in Tamanan district, Bondowoso Regency in the perspective of sharia economic law. This study is expected to provide beneficial input for the development of sharia economic law, so that it can enrich the body knowledge related to sawah (paddy field) mortgage. It is also hoped to give answers to the problems studied and considered as socialization among societies. This study applied qualitative research approach and a field case study was chosen as the research design. The data analysis was performed by using Miles and Huberman analysis model.The results showed that the practice of sawah (paddy field) mortgage in Tamanan district takes place for the reason of urgent need from the society themselves. It is based on the agreement of both parties, rahin and murtahin. The agreement is set forth in the letter of agreement, which rahin borrows money to murtahin with sawah (paddy field) as the bail. The utilization of marhun is handed over to murtahin based on the permission given by rahin until the due date of repayment. When the due date of repayment comes and rahin has not been able to pay off the money, so the utilization of marhun is still taken by murtahin. If it lasts for years and rahin still cannot pay the money, he can sell out the sawah (paddy field) to repay his debts. Based on the perspective of sharia economic law, the practice of sawah (paddy field) mortgage in Tamanan district, Bondowoso regency have fulfilled the elements of an akad (contract in Islam), in which the terms and conditions are agreed upon by both parties; rahin/mortgager and murtahin/sawah (paddy field) owner. The utilization of marhun is taken by murtahin based on the permission of rahin, but in the fact of its utilization, it still contains the element of riba (usury) taking advantages for years. The practice of sawah (paddy field) mortgage in Tamanan district, Bondowoso regency should apply the concept of bay 'al-wafa instead of rahn.